Complain Handling Service Procedure Customer - Rico Arifiyanto (Neo Journal of economy and social humanities, 2022)
The purpose of this study is to find out the service procedures in handling customer complaints, to be able to find out what obstacles are involved in the customer complaints handling service procedures, to be able to find out what solutions can be used related to problems in customer complaints handling service procedures. The research methodology used is descriptive qualitative which aims to describe conditions and analyze customer complaints handling service procedures. In this study, data related to the author's study are sourced from library studies, field studies, and documentation techniques. The results of the study on customer complaints handling service procedures, the authors can conclude that the procedures that have been applied in customer complaints handling services are quite good and effective when carried out in accordance with sequential steps properly and correctly. However, there are still some obstacles that can hinder the procedure, such as the lack of incomplete data. So to deal with these problems, the solution is to contact the customer so they can send photos related to the complaint so that it can be processed immediately and the work can be completed quickly